Case report: Remarkable response to later-line surufatinib in an adult patient with liver metastatic of pancreatoblastoma - Leng, Qingqing; Lv, Wanrui; Yang, Heqi; Li, Xiaofen; Wang, Weiya; Cheng, Ke; Chang, Chen; Cao, Dan (Frontiers in Pharmacology, 2024)
Pancreatoblastoma (PB), a neoplasm derived from pancreatic follicular cells, primarily affects the pediatric population. Although infrequent in adults, it is associated with a considerably worse prognosis. Approximately one-third of patients are diagnosed with metastatic disease, with liver metastases being the most prevalent. Diagnosis relies on histopathological alterations including squamous vesicles, positive staining for CK8/CK18/CK19, and nuclear displacement of β-catenin. Additionally, liver metastases demonstrate substantial enhancement during the arterial phase of a contrast-enhanced computed tomography (CT) scan. Surgical resection serves as the principal therapeutic approach for addressing primary lesions and liver metastatic PB. In instances where surgical intervention is not viable, patients may derive benefits from systemic therapy and radiotherapy. This particular case report presents the clinical details of a 27-year-old female patient diagnosed with PB, who subsequently developed multiple liver metastases following a pancreaticoduodenectomy. Genomic examinations revealed the presence of ERBB2 amplification, RAD54L deletion, low TMB-L, and MSS in the patient. Despite the patient undergoing chemotherapy and Her-2 targeted therapy in conjunction with immunotherapy, no reduction in lesion size was observed until the administration of surufatinib. Subsequently, a notable outcome ensued, where the metastatic lesions were effectively excised via surgical intervention. Surufatinib has demonstrated a progression-free survival (PFS) of no less than 14 months, and the patient’s survival has endured for a duration of 33 months. This indicates the potential efficacy of surufatinib as a viable therapeutic alternative for adult patients afflicted with PB.